Pengaruh Budaya Organisasi dan Kompensasi terhadap Kinerja Karyawan Divisi Kontruksi PT. AL - Rizki Muttaqin; Anik Herminingsih (BISMA (Bisnis dan Manajemen), 2018)
This paper aims to analyze the influence of organizational culture on the performance of employees and compensation at PT. AL. A total of 31 employees of the construction division involved as respondents. Data were obtained through a questionnaire containing closed questions with a Likert scale. Data were analyzed using multiple linear regression. The results showed that the organization culture and compensation has a positive and significant influence on employee performance